Biomechanical Test of Three Methods to Treat Thumb CMC Arthritis - Putnam, Matthew D.; Rattay, Richard; Wentorf, Fred (Journal of Wrist Surgery, 2014)
Background Basilar thumb arthritis, or first carpometacarpal arthritis, is a common condition, predominantly affecting women. Surgical treatment of this condition is highly varied. One common method consists of trapezium excision and a concomitant procedure for treatment of the “floating” thumb metacarpal. That procedures vary suggests that no method has an “outcome” advantage over another. However, the frequency of side effects is higher in more complex procedures.Question/Purposes We speculated that in vitro testing might identify a potential outcome difference that has been difficult to measure in vivo. Since the more complex procedure to treat this condition has a higher frequency of clinical side effects, we hoped to determine its functional value compared with less complex procedures.Methods A two-degrees-of-freedom biomechanical cadaver study examined simulated pinch strength and metacarpal subsidence during pinch. Three methods were compared with each other and against the normal pretreatment state: trapezial excision alone; trapezial excision and suture suspensionplasty (TESS); and trapezial excision followed by a ligament reconstruction using one-half of the flexor carpi radialis and tendon interposition (LRTI).Results After TESS, the loaded mean height of the arthroplasty space was 1.20 cm. This was statistically less than the pretreatment height of 1.50 cm (P < 0.05). However, the height maintained after LRTI (1.00 cm) was also statistically less than pretreatment state (P < 0.05) and less than TESS (P < 0.05). Trapezial excision alone was least successful at maintaining height. In contrast, the mean key pinch measured after treatment could not be predicted by treatment employed.Conclusions In summary, the tested technique of TESS appears to be biomechanically sound as related to maintenance of first metacarpal height. In in vitro testing it is superior to excision alone and at least equal to the ligament reconstruction method tested. Analysis of our data shows that 96% of the overall height (distance) maintained post excision is explained by surgical state.Clinical Relevance Trapezial height is preserved using support schemes in a laboratory setting. In the in vivo postsurgical state, clinical intrinsic muscle function may be superior when support is used compared with trapeziectomy alone.
Keywords: Basilar thumb arthritis; first carpometacarpal (1st CMC) arthritis; in-vitro testing; biomechanical cadaver study; trapezial excision